Crystal Methamphetamine Use and Initiation among Gay, Bisexual, and Other Men Who Have Sex with Men Living with HIV in a Treatment as Prevention Environment. (15th October 2020) - Colyer, Sean P.; Moore, David M.; Cui, Zishan; Zhu, Julia; Armstrong, Heather L.; Taylor, Matthew; Edward, Joshua; Howard, Terry; Dickie, Chad; Olarewaju, Gbolahan; Montaner, Julio S.G; Hogg, Robert S.; et al.
Abstract: Background: Risk compensation in an HIV Treatment as Prevention (TasP) environment may increase high-risk sexual and substance use behaviors among people living with HIV. Objective: To examine recent crystal methamphetamine (CM) use/initiation in a longitudinal cohort of gay, bisexual, and other men who have sex with men (GBMSM) living with HIV in Metro Vancouver, Canada. Methods: Eligible participants were GBMSM aged >15  years who reported sex with another man in the past six months. Participants were recruited using respondent-driven sampling and self-completed a computer questionnaire every six months. We used multi-level generalized mixed-effect models to evaluate trends in recent CM use (past six months), multivariable logistic regression to identify covariates of recent CM use, and multivariable survival analysis to identify predictors of CM initiation. Results: Of 207 GBMSM living with HIV at enrollment, 44.3% reported recent CM use; there was a statistically non-significant decrease over the study period (41% in first period to 25% in final period, p   =  0.087). HIV treatment optimism was not associated with CM use/initiation. CM use was positively associated with depressive symptomology, sexual escape motivation, transactional sex, number of anal sex partners, condomless anal sex with seroconcordant partners, STIs, and other substance use. Recent CM use was negatively associated with viral load sorting. CM initiation was predicted by escape motivation, transactional sex, and group sex participation. Conclusion: Results suggest that CM use among GBMSM living with HIV is prevalent and increased CM use/initiation is not a consequence of TasP public policy.